Kingston: A Societal Patchwork - Jérémie Kroubo Dagnini (Études Caribéennes)
Besides the designations of numerous Kingston’s neighborhoods – Trench Town, Jones Town, Denham Town, Rae Town, August Town etc. – that clearly refer to the names of towns (in the city), the Jamaican capital is divided into two distinct sections, uptown, the northern part where the wealthiest residents live, and downtown, the historic city center situated near the waterfront which accommodates the low-income population. This ‘urban fragmentation’ examined by Romain Cruse (2010) and Rivke Jaffe (2016) actually gave rise to a true societal patchwork highlighting identity, social, political, religious and musical issues. Thus, this paper intends to study Kingston through the prism of differentiation and societal segmentation.